A Second-Order ΣΔ ADC using sputtered IGZO TFTs with multilayer dielectric - Correia, Ana Paula Pinto (2014)
This dissertation combines materials science and electronics engineering to implement, for the first time, a 2nd-order ∑∆ ADC using oxide TFTs. The transistors employ a sputtered IGZO semiconductor and an optimizeddielectric layer, based on mixtures of sputtered Ta2O5and SiO2. These dielectrics are studied in multilayer configurations, being the best results achieved for 7 layers: IG<10 pA and EB>7.5 MV/cm, while keeping κ>10, yielding a major improvement over Ta2O5single-layer. After annealing at 200 °C, TFTs with these dielectrics exhibit μSAT≈13 cm2/Vs, On/Off≈107and S≈0.2 V/dec. An a-Si:H TFT RPI model is adapted to simulate these devices with good fitting to experimental data. Concerning circuits, the ∑∆ architecture is naturally selected to deal with device mismatch. After design optimization, ADC simulations achieve SNDR≈57 dB, DR≈65 dB and power dissipation, approximately, of 22 mW (VDD=10 V), which are above the current state-of-the-art for competing thinfilm technologies, such as organics or even LTPS. Mask layouts are currently under verification to enable successful circuit fabrication in the next months.This work is a major step towards the design of complex multifunctional electronic systems with oxide TFT technology, being integrated in ongoing EU-funded and FCT-funded research projects at CENIMAT and UNINOVA.